2023
DOI: 10.7759/cureus.41713
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Complications Following Chronic Patellar Tendon Repair: A Systematic Review

Abstract: The purpose of this systematic review is to report outcomes and complications following the reconstruction of chronic patellar tendon ruptures. Four databases (Cochrane Database of Systematic Reviews, PubMed, Embase, MEDLINE) were searched from inception to July 2021. Inclusion criteria included articles that (1) analyzed outcomes and complications following chronic patellar tendon reconstruction (>4 weeks from injury to repair), (2) were written in English, (3) greater than five patients, and (4) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…B ilateral PTR is a severe injury with significant impact on patients' private and professional lives 6 . It was recently demonstrated that the use of suture anchors compared with transosseous sutures can decrease the rerupture rate 7 .…”
Section: Discussionmentioning
confidence: 99%
“…B ilateral PTR is a severe injury with significant impact on patients' private and professional lives 6 . It was recently demonstrated that the use of suture anchors compared with transosseous sutures can decrease the rerupture rate 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Tendons are important tissues that connect muscles and bones and play roles in transmitting strength and maintaining body movement [ 1 , 2 ]. Tendons are prone to injury owing to various conditions, such as excessive exercise, trauma, diabetes, aging, and even rupture, leading to pain and motor dysfunction [ 3 , 4 ]. Moreover, tendon tissues are characterized by poor cellularity and vasculature, which hinder and complicate the healing of tendon injuries [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conservative treatment requires a long recovery period and often fails to fully restore tendon structure and function [ 11 ]. Although surgical repair can better address injured tendons, postoperative complications and tendon adhesion also occur [ 4 , 12 ]. Therefore, the effective repair of injured tendons and promotion of tendon regeneration have become important and challenging issues in this field in recent years.…”
Section: Introductionmentioning
confidence: 99%